2017
DOI: 10.14814/phy2.13288
|View full text |Cite
|
Sign up to set email alerts
|

Acute impact of drinking coffee on the cerebral and systemic vasculature

Abstract: Previous studies have suggested that the risk of ischemic stroke increases immediately after drinking coffee. Indeed, drinking coffee, that is, caffeine, acutely increases arterial stiffness as well as blood pressure and peripheral vascular resistance. On the other hand, it has been reported that arterial stiffening is associated with elevation in the pulsatility index (PI) of cerebral blood flow (CBF), which increases the risk of brain disease. However, the effect of drinking coffee on the PI of the CBF and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…After a 10-min baseline measurement, the participant would drink either coffee or the placebo. The study showed that mean arterial pressure and systolic blood pressure were higher at times of 30 and 60 min after drinking the coffee when compared to the placebo [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…After a 10-min baseline measurement, the participant would drink either coffee or the placebo. The study showed that mean arterial pressure and systolic blood pressure were higher at times of 30 and 60 min after drinking the coffee when compared to the placebo [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…14 However, the analysis adjusted for some cardiovascular risk factors suggests a direct action of coffee on vessels. 3,14,15 Rhee et al 16 found that caffeinated coffee, decaffeinated coffee, and caffeine are not risk factors for hypertension in postmenopausal women. The European Food Safety Authority recently published a scientific opinion on the safety of caffeine and noted that caffeine consumption, at single doses ranging from 80 to 300 mg, acutely increases BP, which reaches a peak 30 min after consumption and then returns to baseline after 2-4 h in the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, a study conducted by Mostofsky et al [ 270 ] found an increase in the hazard ratio of an ischemic stroke within 60 min after drinking coffee. Likewise, an acute increase in the risk of ischemic stroke was observed immediately after drinking coffee by Washio et al [ 271 ], but as these authors emphasized, the reason of observed coffee impact may be caused by other factors rather than an elevation in pressure in the cerebral circulation [ 271 ].…”
Section: Neuroprotective Effects Of Coffee Bioactive Compoundsmentioning
confidence: 99%